Examining Concrete Manipulative Effectiveness: Magic Glass Media in Fourth-Grade Multiplication Instruction - Devinta Tri Utami Geger Haryanto; Azizah Azizah; Nuraini Nuraini; Nurul Fitriah Aras; Sukri Sukri (Papanda Publisher, 2026)
Multiplication instruction in elementary schools often relies on abstract presentations without adequate concrete support, resulting in low student achievement. This study investigated the effect of magic glass learning media on fourth-grade students' multiplication learning outcomes at SD Inpres 1 Tondo. A pre-experimental one-group pretest-posttest design was employed with 26 fourth-grade students selected through saturated sampling. Data were collected using a 20-item multiple-choice test with established content validity (CVI > 0.78) and reliability (α = 0.82). Students completed a pretest, participated in four instructional sessions using magic glass media representing multiplication as repeated addition through cups and counting sticks, then completed a posttest. Data analysis utilized descriptive statistics and paired-samples t-test (α = 0.05) following Shapiro-Wilk normality testing. Mean scores increased significantly from 35.40 (SD = 15.19) to 75.78 (SD = 18.65), representing a 114% improvement. The paired-samples t-test revealed statistically significant differences (t = -11.251, df = 25, p < 0.001). Low-performing students demonstrated particularly dramatic gains, while engagement remained consistently high throughout treatment sessions. Findings confirm that magic glass media effectively enhances multiplication learning by aligning with students' concrete operational developmental stage, consistent with Piagetian and Brunerian theories. The media facilitates meaningful conceptual understanding through hands-on manipulation, particularly benefiting struggling learners. Magic glass learning media represents an accessible, evidence-based intervention for improving elementary mathematics instruction.